Driving operational excellence: Cultivating organizational culture in smes manufacturing sectors. - Abdul Wahab, Mohd Hafeez Al-Amin; Che Cob, Che Mohd Syaharuddin; Yaacob, Abdul Aziz; Yusri, Muhammad Yushafiq; Mohamad, Mohamad Sukram (International Journal of Accounting, Finance and Business, 2025)
This study aims to explore the impact of organizational culture on operational excellence in the manufacturing sector of Small and Medium Enterprises (SMEs) in Malaysia. Specifically, this study investigates three dimensions of organizational culture namely empowerment, team orientation and capability development which are believed to drive positive organizational change and foster excellent performance. The study proposes a conceptual framework that integrates these dimensions of organizational culture to enhance operational excellence. Additionally, it contributes significantly to existing knowledge by deepening the conceptual understanding of operational excellence within the context of Malaysian SMEs in the manufacturing sector. The practical implementation of effective management strategies incorporating organizational culture among Malaysian SMEs has the potential to greatly improve operational excellence and overall business performance. The findings offer valuable insights for SME manufacturers in Malaysia as well as entrepreneurs and policymakers interested in enhancing the competitiveness and resilience of the manufacturing sector through the cultivation of a high-performing organizational culture.